2022
DOI: 10.3390/horticulturae8111002
|View full text |Cite
|
Sign up to set email alerts
|

Response and Function of Solanum lycopersicum L. SlSGR2 Gene under Cadmium Stress

Abstract: Cd stress can cause severe damage to the chloroplast structure and plant function. The chloroplast stay-green gene (SGR2) is senescence-inducible and has several important functions such as regulating senescence, responding to abiotic stress, and regulating seed and fruit ripening. The SlSGR2 gene was cloned from the tomato “Hongluocheng” (full-length of 819 bp encoding 272 amino acids). Subcellular localization prediction and laser confocal observation revealed that the SlSGR2 protein was localized to the chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
2
0
1
Order By: Relevance
“…The prediction of subcellular localization showed the probability of this protein being located in mitochondria. This is inconsistent with the results of previous studies on the subcellular localization of the SGR protein in tomatoes [46], Zoysia japonica [47], rice [25] and Tribulus terrestris alfalfa [48]. Therefore, we further confirmed the subcellular localization of MdSGR2 by fusion reporter gene analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The prediction of subcellular localization showed the probability of this protein being located in mitochondria. This is inconsistent with the results of previous studies on the subcellular localization of the SGR protein in tomatoes [46], Zoysia japonica [47], rice [25] and Tribulus terrestris alfalfa [48]. Therefore, we further confirmed the subcellular localization of MdSGR2 by fusion reporter gene analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in this study, we found that MdSGR2 negatively regulates chlorophyll degradation. The function of MdSGR2 is consistent with that of SGR2 studied by Ma et al [46] in tomatoes and by Sakuraba et al [20] in Arabidopsis. Sakuraba et al [20] overexpressed the SGR2 gene in Arabidopsis and found that the plants showed an evergreen phenotype, and the sgr2-1 knockout mutant had advanced leaf yellowing under natural aging.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation